The Urgency of Enforcing Retitution Obligations for Victims of Sexual Violence in the Indonesian Criminal Legal System - Novrian, Bayu (KnE Social Sciences, 2025)
Restitution is a form of restoration of victims’ rights that is starting to receive serious attention in the Indonesian criminal law system, especially in cases of sexual violence. So far, legal attention has focused more on perpetrators of crimes, while the restoration of victims’ rights has not been fully accommodated optimally. This research aims to analyze the procedures for implementing restitution and its urgency for victims of sexual violence based on Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence (UU TPKS). The research method used is normative juridical with a statutory approach and legal literature as the main data sources. The research results show that the TPKS Law clearly stipulates the obligation of restitution as part of criminal decisions, both against individuals and corporations. Restitution includes compensation for the victim’s material and immaterial losses, as well as medical and psychological treatment costs. The security confiscation and asset auction mechanisms are regulated to ensure legal certainty regarding the implementation of restitution. If the perpetrator is unable to pay, the state is obliged to provide compensation according to the verdict. However, in practice, law enforcement officials often ignore the inclusion of restitution in demands or decisions. Fulfilling restitution in the future requires the active role of prosecutors in demanding restitution, as well as full support from the justice system to make restitution an inseparable part of substantive justice for victims of sexual violence.